2010
DOI: 10.1111/j.1538-7836.2010.04029.x
|View full text |Cite
|
Sign up to set email alerts
|

Improved performance characteristics of the von Willebrand factor ristocetin cofactor activity assay using a novel automated assay protocol

Abstract: Willebrand factor ristocetin cofactor activity assay using a novel automated assay protocol. J Thromb Haemost 2010; 8: 2216-23.Summary. Background, objectives and methods: An accurate, sensitive and precise assay for reliable determination of the ristocetin cofactor activity of von Willebrand factor (VWF:RCo) in plasma and von Willebrand Factor (VWF)-containing concentrates has been evaluated. The assay is based on a commercially available automated protocol with modifications including a combination of adding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
35
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(38 citation statements)
references
References 22 publications
2
35
1
Order By: Relevance
“…Here, there is at least a potential solution, given recently reported vWF:RCo assay improvements. 8,9 Although lower limit of detection is notably better using vWF:antigen, vWF:CB, and vWF:Act assays, laboratories will still have difficulty accurately identifying vWF values between 0 and 10 U/dL. 7 Fourth, although the vWF:CB was found to provide the best discrimination of types 1 and 2 vWD by Chandler et al, 1 in support of previous findings, it was interesting that this was achieved using commercial kits that have been found to be less optimal in direct vWF:CB comparison assessments.…”
mentioning
confidence: 99%
“…Here, there is at least a potential solution, given recently reported vWF:RCo assay improvements. 8,9 Although lower limit of detection is notably better using vWF:antigen, vWF:CB, and vWF:Act assays, laboratories will still have difficulty accurately identifying vWF values between 0 and 10 U/dL. 7 Fourth, although the vWF:CB was found to provide the best discrimination of types 1 and 2 vWD by Chandler et al, 1 in support of previous findings, it was interesting that this was achieved using commercial kits that have been found to be less optimal in direct vWF:CB comparison assessments.…”
mentioning
confidence: 99%
“…34 A few assays have taken advantage of GPIb binding independent of ristocetin through using recombinant human GPIb with 2 gain-of-function mutations inserted. 12,13,35 Flood et al have described the VWF:IbCo assay, which demonstrated a CV of 7% and lower limit of detection of 3 U/dL.…”
Section: Discussionmentioning
confidence: 99%
“…Automation of VWF:RCo appears to improve precision, but in general does not improve LOD issues [24], and does not seem to protect laboratories against VWD identification errors [26,27]. However, a recently reported modification to automated VWF:RCo testing would appear to have largely overcome the LOD problem, with this now reported to be as low as 2 U/dl in recent testing [47,48].…”
Section: Technical Considerations Strengths and Limitations Of Diffementioning
confidence: 97%
“…Historically, VWF:RCo was first utilized as an agglutination assay primarily in platelet aggregometers or using a manual visual slide agglutination procedure; both of these methods are laborious. VWF:RCo by platelet agglutination has also been successfully automated on many modern haemostasis analysers, including the Siemen's BCS, IL ACL instrumentation, Stago STAR and most recently the Sysmex CA-2000i/CA2100i instruments [41][42][43][44][45][46][47][48]. Methods for VWF:RCo based on flow cytometry have also been described [49,50], as have ELISA-based methods [51][52][53].…”
Section: Technical Considerations Strengths and Limitations Of Diffementioning
confidence: 99%
See 1 more Smart Citation